Frisco, Youre A Bear - Arthur Don and Jack E. McClellan::::::::: (Wall, McClellan Music Publishing Co.)
Piano and vocal score, 6 p. At head of title: Respectfully dedicated by the composers to the Panama-Pacific Exposition Committee. On cover: Sung & featured by Tom Kelly, a California boy, with his port. Also on cover is a G. Moulon photo captioned Raising four million dollars in two hours, Merchants Exchange, San Francisco, April 28, 1910. Publishers advertisements on p.[2] and verso of last leaf.